Teknik Pembesaran Kepiting Bakau (Scylla sp.) di Teluk Pangpang Kabupaten Banyuwangi - Dewi Mutamimah; Yuyu Wahyudin (Yayasan Literasi Sains Indonesia, 2023)
Mangrove is one of the unique and distinctive ecosystems, found in tidal areas of coastal areas, coasts and small islands with very high natural resource potential. Mangroves live on sandy or muddy substrates. Lots of organisms that live in the mangrove environment, one of which is the mud crab. Mud crabs have high economic value in the domestic and international markets, encouraging fishermen to start cultivating mud crabs in ponds. The purpose of this research was to determine the magnification technique of mud crabs (Scylla sp.) in Pangpang Bay, Banyuwangi Regency. The research method used is descriptive method with data collection techniques through primary data and secondary data. Data collection was carried out by observation, interviews, active participation, and literature study. The results of the study were mud crab seeds were obtained from collectors in the Muncar District of 1 quintal for a pond with an area of 50 m x 100 m. Maintenance of mud crabs in Pangpang Bay Pond includes feeding and regulating water circulation. The resulting mud crab weight was divided into 3 grades, namely grade A (150-250 g), grade SP 1 (250-350 g) and SP 2 (350 – 500 g).